História e ficcção: na minissérie Anos Rebeldes - Melo, Ana Cláudia Peixoto de (2006)
The present work s main objective is to analyze the miniserie Anos Rebeldes,in wich it s most important theme is the military dictatorship, retaking recent questions still in the memory of those who had lived deeply the so called Lead Years . In Anos Rebeldes the ficcional narrative is used, considering not only the production, but also historical facts related with the miniserie. Having as theoretical recital the approaches of Cultural History, this research wants to understand, by means of the historiographical possibilities and contributions of other knowledge fileds, the relation between history and fiction, that is, to unveil how historical facts are treated and how its different nuances are incorporated by cultural industry, particularly television. This way, this present inquiry consists the result of the interaction with different knowledge fields, in order to understand how the television format, in this case, a miniserie, locks History and its gamma of interpretations.